2021
DOI: 10.1002/ctm2.349
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic colorectal cancer‐derived extracellular vesicles deliver microRNA‐361‐3p to facilitate cell proliferation by targeting TRAF3 via the noncanonical NF‐κB pathways

Abstract: This study first confirmed the key role of miR-361-3p in hypoxic EVs in promoting proliferation and inhibiting apoptosis of CRC cells. • miR-361-3p promotes CRC progression by targeting the TRAF3-mediated noncanonical NF-kB pathway. • HIF-1α is the key factor for hypoxic exosomal miR-361-3p elevation in CRC cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…The aberrant regulations of the cell cycle, cell apoptosis, and metastatic behaviors have played critical roles in the proliferation and progression of tumors [ 19 , 31 , 33 , 34 ]. Some studies revealed that circRNAs play key roles in the regulation of the cell cycle, cell apoptosis, and distant metastases of CRC [ 11 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aberrant regulations of the cell cycle, cell apoptosis, and metastatic behaviors have played critical roles in the proliferation and progression of tumors [ 19 , 31 , 33 , 34 ]. Some studies revealed that circRNAs play key roles in the regulation of the cell cycle, cell apoptosis, and distant metastases of CRC [ 11 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…TUNEL assay was performed as previous description [ 19 ]. The nucleus of the cell was stained by DAPI.…”
Section: Methodsmentioning
confidence: 99%
“…Lung cancer is characterized by sustained cell proliferation, resistance to cell death, invasion and metastasis ( Hanahan and Weinberg, 2011 ). Intratumoral hypoxia is a critical microenvironmental factor driving cancer progression and is associated with poor clinical prognosis ( Taiakina et al, 2014 ; Schito and Semenza, 2016 ; Li et al, 2021 ). Hypoxia upregulates a large number of oncogenes that contribute to the excessive proliferation, invasion, metastasis, and so on ( Wigerup et al, 2016 ; Mennerich et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that hypoxic colorectal cancer-derived extracellular vesicles deliver microRNA-361-3p to facilitate cell proliferation by targeting TRAF3 via the noncanonical NF-κB pathways [74].…”
Section: Exosome In Radio-resistancementioning
confidence: 99%